Enhancing University EFL Speaking and Listening Skills through AI-Based Conversational Tools - Naila Lutfia; Edi; Fauzi Bafadal (Universitas Sulawesi Barat, 2026)
Artificial intelligence (AI)-based conversational tools are increasingly being integrated into English as a Foreign Language (EFL) learning because they offer flexible opportunities for language practice and immediate feedback. However, limited research has explored how university EFL students perceive the use of these tools to support speaking and listening development within the Indonesian higher education context. This study aimed to investigate EFL students' perceptions and experiences of using AI-based conversational tools, particularly ChatGPT, to support English speaking and listening learning. The study employed a qualitative descriptive design supported by descriptive questionnaire data. Thirteen undergraduate EFL students (8 females and 5 males), aged 19–23 years, from Muhammadiyah University Mataram, Indonesia, participated in the study. Data were collected through a five-point Likert-scale questionnaire and semi-structured interviews and analyzed using descriptive statistics and thematic analysis. Three major themes emerged from the findings. First, participants perceived that AI-based conversational tools promoted learner autonomy and confidence by providing immediate feedback, flexible opportunities for independent practice, and a supportive environment for speaking and listening practice. Second, participants reported that AI tools assisted with grammar, vocabulary, pronunciation, and listening comprehension but were less effective in addressing the sociolinguistic and contextual nuances of authentic communication. Third, participants perceived AI-based conversational tools as valuable complements to classroom instruction by encouraging more active participation and self-directed learning rather than replacing lecturer-guided interaction. These findings suggest that AI-based conversational tools are perceived by students as useful supplementary resources for supporting English language learning. The study contributes context-specific evidence from Indonesian higher education and offers practical implications for educators seeking to integrate AI-based conversational tools into EFL teaching while maintaining the essential role of authentic human interaction in language development.